Reological model and hauling diagram of deformed by friction contact solid bodies in the time of transition from rest to motion without lubricant - Пожбелко, В.И. (Problems of Tribology, 2014)
The paper presents modeling and analysis of time-velocity dynamic characteristics of static and kinetic friction as well as general diagram describing transition machine and mechanisms from rest to motion without lubricant which following reflection in machine and mechanisms preliminary displacement contents elastic and elastic-plastic deformation with districts of external and inside fiction, as well as dynamics of friction pair in various duration of motionless friction contact, hauling velocity and elasticity of driving mechanical system